Evaluation of the Effectiveness of the Internal Control System at KSP Kopdit Tuke Jung Nele - Ni Putu Ayu Wedani; Yosefina Andia Dekrita; Henrikus Herdi (International Publisher (YAPENBI), 2025)
This study aims to evaluate the effectiveness of the internal control system applied to the Kopdit Tuke Jung Nelle Savings and Loan Cooperative (KSP). A sound internal control system is essential to ensure the achievement of organizational goals, including asset protection, reliability of financial statements, and compliance with applicable regulations and regulations. The evaluation was carried out using the COSO (Committee of Sponsoring Organizations of the Treadway Commission) framework, which includes five main components: control environment, risk assessment, control activities, information and communication, and monitoring. Data was collected through interviews with management, observation of operational processes, and analysis of documents related to policies and procedures. The results of the evaluation show that although most of the components of the internal control system are running well, there are still some weaknesses in terms of monitoring and supervision of policy implementation. Therefore, it is recommended that KSP Kopdit Tuke Jung Nelle strengthen the monitoring and training mechanism for all employees to improve the effectiveness of the overall internal control system.